ANALYSIS OF SPECIFIC VERTICAL AND ANGLE VIBRATIONS OF A SCREW CONVEYOR SHAFT MOUNTED ON SLEEVE BEARING SUPPORTS - Jumaev , Akbarjon; Ergasheva , Gozal; Abdumanonov , Samandar (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This paper presents an analysis of the natural vertical and inclined vibrations of a screw conveyor shaft mounted on elastic bearing supports. The performance of the proposed double-flight screw conveyor is mainly determined by the screw parameters, including diameter, rotational speed, length, screw pitch, as well as the amplitude and frequency of waves in each screw flight. The study investigates the influence of these parameters on the vibration characteristics and proposes scientific and technical solutions aimed at ensuring stable and efficient operation of the conveyor. The obtained results are of practical importance for the design and performance improvement of screw conveyor systems.